Assessing Vulnerability of Fish in the U.S. Marine Aquarium Trade - Dee, Laura E.; Karr, Kendra Anne; Landesberg, Celia J.; Thornhill, Daniel J. (Frontiers in Marine Science, 2019)
The trade in coral reef fishes for aquariums encompasses over 1,800 species from over 40 exporting countries, yet the population status for most traded species is unknown and unevaluated. At the same time, these coral reef fishes face a growing number of threats and often occur in jurisdictions with limited management capacity and data. In response, we assess vulnerability to overfishing for 72 coral reef fishes popular in the aquarium trade for the United States – the top importer – from the top exporting countries (Indonesia and the Philippines). We use a data-limited assessment approach: productivity susceptibility analysis (PSA). PSA estimates relative vulnerability of species by assessing their biological productivity and susceptibility to overfishing. The most and least vulnerable stocks were differentiated by attributes related to the reproductive biology (e.g., breeding strategy, recruitment pattern, and fecundity), appropriateness, ease of capture (e.g., schooling and aggregation), and rates of natural mortality. Our analysis identifies several of the most and least vulnerable species popular in the aquarium fish trade. The species that ranked as least vulnerable to overcollection were Gobiodon okinawae, Nemateleotris magnifica, Gobiodon acicularis, Salarias fasciatus, Ptereleotris zebra, Gobiodon citrinus, Pseudocheilinus hexataenia, Chaetodon lunula, Nemateleotris decora, and Halichoeres chrysus. In contrast, the ten most vulnerable species were Chromileptes altivelis, Plectorhinchus chaetodonoides, Pterapogon kauderni, Premnas biaculeatus, Echidna nebulosa, Centropyge bicolor, Zebrasoma veliferum, Pomacanthus semicirculatus, Zebrasoma scopas, and Thalassoma lunare. In a data-limited context, we suggest how these vulnerability rankings can help guide future efforts for reducing vulnerability risk. In particular, species that are relatively high-vulnerability and high-volume are prime targets for research and aquaculture efforts, increased monitoring of collection and exports, species-specific stock assessments, and voluntary reductions by retailers and consumers to avoid overexploitation.